Analysis of ground response and potential seismic damage to sites surrounding Cimandiri Fault, West Java, Indonesia - Mase, Lindung Zalbuin; Somantri, Andri Krisnandi; Chaiyaput, Salisa; Febriansya, Aditia; Syahbana, Arifan Jaya (My University, 2023)
Cimandiri Fault in West Java is one of the active faults in West Java, Indonesia. The activity of the fault could potentially result in damage to the surrounding areas. This paper presents a study of ground response analysis and the potential seismic damage to structures in sites surrounding the Cimandiri Fault. The site investigation data are collected. Furthermore, ground motion prediction is conducted. To estimate the potential damage, the potential seismic damage is performed. The spectral matching method determines artificial ground motion represented by the investigated sites. The seismic ground response analysis is conducted to observe ground motion parameters and soil response. The results show that the prediction of damage intensity level in the study area is about Scale VIII at maximum. The site amplification during seismic response is observed to vary from 1.4 to 2.7. The results also show that spectral acceleration design is still reliable in covering the effect of spectral acceleration amplification. However, the results also indicate that the trend of spectral acceleration shows that the amplification generally occurs at a medium-long period. It implies that the resonance effect may occur in medium-high-rise buildings.
Keywords: Cimandiri fault; Ground response; Seismic damage; Site amplification